ANALISIS KARAKTERISTIK PERUSAHAAN, INTENSITAS ASET TETAP DAN KONSERVATISME AKUNTANSI TERHADAP TAX AVOIDANCE - Avita Nia Ningsih; Wiwit Irawati; Harry Barli; Angga Hidayat (Universitas Pamulang, 2019)
This study aims to obtain empirical evidence about the influence of Company Characteristics, Intensity of Fixed Assets and Accounting Conservatism on Tax Avoidance. The independent variables used are Company Characteristics, Intensity of Fixed Assets and Accounting Conservatism. The dependent variable used is Tax Avoidance. The population in this study is mining companies listed on the Indonesia Stock Exchange in the 2014-2018 period. Samples collected by purposive sampling method. The number of companies sampled in this study were 13 companies. The method of analysis of this study uses multiple linear regression. The results of research conducted indicate that the variable Company Characteristics influence on Tax Avoidance, Fixed Asset Intensity has no effect on Tax Avoidance and Accounting Conservatism has no effect on Tax Avoidance. Simultaneously all free variables (Characteristics of Company, Fixed Asset Intensity and Accounting Conservatism) affect the Tax Avoidance.Keywords: Company Characteristics; Fixed Assets Intensity; Conservatism Accounting; Tax Avoidance.